Notes on the Ecuadorian media debate: Distribution of broadcasting frequencies, possibilities for "educommunication - Roberto Sánchez Montoya (Universidad Politécnica Salesiana, 2013)
In the last few years, some progressive countries in Latin America have made changes to laws that regulate media, with a particular emphasis on audiovisual media that make use of radio broadcasting space. A key feature shared by these new media laws is the criteria for reallocating radio and TV concessions, with a compromise of assigning a third of these frequencies to non governmental organizations, referred to as community media. Moreover, in several cases, as in Ecuador, another third of the frecuencias are reserved for public institutions. These changes would allow, in the medium term, for community and public groups to own most of the range of audiovisual media frequencies in several countries in the region. In theory, we would have spaces that had been previously hoarded by the private sector, now in the hands of groups outside of the strictly commercial rationality used for their own benefit. In this context, we ask, what possibilities are there for a relaunch of communication proposals oriented, in the general sense, to "educommunication" (educational communication)? We will attempt to provide answers by using Ecuador as a reference for both challenges, learned successes, and limitations under the new Law of Communication.